(untitled) (Research, Society and Development, 2021)
This randomized clinical trial evaluated an intracanal medicinal paste based on Ca(OH)2 and Aloe vera in necrotic teeth with periapical lesions. Sixty-four teeth, from 60 patients, were divided according to the intracanal medication used: Control (Ca(OH)2 and saline solution), and experimental (Ca(OH)2 and Aloe vera). Endodontic instrumentation and insertion of intracanal medication were performed according to the group. After 15 days, the teeth were filled and restored. Postoperative symptoms were assessed following a pain scale. Clinical and radiographic evaluation was performed at three, six and nine months after treatment. Treatments were classified into success (those with partial or complete healing) and failure. For statistical analysis of postoperative pain between groups, the Mann-Whitney test was used. The intragroup analysis used the Friedmann test. To assess treatment success, the chi-square test was used. It was considered significant p<0.05. Forty-eight patients, one tooth in each, completed the study. Postoperative pain values ​​at 04 and 24 hours were significant for the Aloe vera group (p<0.001), with no statistical difference between groups (p=0.307) at 48 hours. After nine months, success rates were 95.8% for the experimental group and 83.3% for the control, with no significant difference (p=0.348). Aloe vera and Ca(OH)2 paste provided remission of postoperative pain, without significant clinical and radiographic changes. Aloe vera is believed to be an alternative vehicle for calcium hydroxide as an intracanal medication.